Results and findings in the socio-economic determinants of adolescent pregnancy in Katutura, Windhoek: Namibia - Amakali-Nauiseb, Taimi; Jaswa, Susie-Ubomba (International Journal of Health, 2017)
This study focuses on the results and findings in the study on socio-economic determinants of adolescent pregnancy in Katutura, Windhoek: Namibia.The aim of this study was to analyze and to come forth with results and findings to explore the socio-economic determinants of adolescent pregnancy in Katutura, Windhoek: Namibia.The clinical study was a cross-sectional, descriptive study of three months duration. Semi-structured interviews methods were utilized to collect the data. A random sampling method was use to select the participant. Study population was all pregnant women attending the Katutura antenatal clinic during the time of the study. The study sample of 150 pregnant adolescent were accepted into the study. Inclusion and exclusion criteria were adhered in the selection process. Data analysis; qualitative and quantitative thematically analysis was used to interpret the data.Based on the findings of the study 89% of the pregnant adolescent falls between the ages 17-21 who visited the ante -natal clinic. The majority interviewed represents 65% of the highest-grade completed grade 8-10. 79% of the pregnant adolescents were still living with their parents. The mean age of the first intercourse was 16.5 years. 71% represent their first pregnancy, compare to 29 % who said this was their second pregnancy. 46% plan to give their babies away, to their mothers which represent 84, 7%. 54 % of the pregnant adolescent prefer to take up their parental role, responsibility and accountability compare to the 46 %, shifting their roles to extended families.